(untitled) (Plant Tissue Culture and Biotechnology, 2017)
An efficient rapid in vitro regeneration protocol was described from nodal segment, leaf and petiole explants. MS medium supplemented with 1.0 mg/l BAP and 0.5 mg/l IAA was found best for the multiple shoot formation from nodal segments. In this combination 99% explants produced multiple shoots and the average number of shoots per explants was 20.1 ± 1.96. For petiole and leaf explants best response was observed on MS supplemented with 2.0 mg/l BAP, 1 mg/l IAA and 0.5 mg/l Kn. Petiole explants produced highest mean number of shoots/explant (22.9 ± 1.728) among the three explants when the explants were cultured on MS with 2.0 mg/l BAP, 1 mg/l IAA and 0.5 mg/l Kn. The highest frequency of root induction (100%) and mean number of roots/plantlets (11.75) were obtained on MS. The rooted plantlets were transferred for hardening following acclimatization and finally were successfully established in the field. Plant Tissue Cult. & Biotech. 27(2): 207-216, 2017 (December)